(untitled) (Philological Studies, 2023)
The article analyses the specific concept of the ‘place with a mystery’ developed in the works of Daniela Hodrová and applies it to the novels of contemporary Czech authors, Josef Pánek, Matĕj Hořava, and Anna Cima. The aim of the article is to establish the connection between the novels in terms of the shift in meaning and the symbolism of the ‘places with a mystery’, which may be the foundations of the new existentialist branch of contemporary Czech fiction.